Direct and Indirect Speech Acts on Boris Bokir and Pache Justeen Podcasts - Izar, Sri Listiana; Nasution, Muhammad Muslim; Izar, Julisah; Khasanah, Desi Nur (English Department, Faculty of Humanities, Andalas University, 2023)
This study intends to describe direct speech acts and indirect speechacts on the Boris Bokir and Pachee Justeen Podcasts. This study used a qualitative descriptive approach. The research data were in the form of sentence excerpts originating from utterances made by Boris Bokir and Pache Justeen. The data then collected by using the note-taking technique First, the researcher listened to video recordings of Boris Bokir and Pache Justeen's podcats, then listened and took notes simultaneously. Furthermore, the acquisition of research data obtained that the speech act groups used by Boris Bokir and Pache Justeen contain direct and indirect speech acts. The direct and indirect speech acts consist of three modes, declarative sentences, interrogative sentences, and imperative sentences.The utterances made by Boris Bokir and Pache Justeen on podcats have a purpose that is in line with the function of the speech.